Improved performance of agriculture in Africa South of the Sahara: Taking off or bouncing back? - Nin-Pratt, Alejandro; Johnson, Michael E.; Yu, Bingxin (International Food Policy Research Institute, 2012)
The improved performance of the agricultural sector in Africa south of the Sahara during the most recent decade (2000–2010) has raised questions about the drivers behind the growth. Skeptics argue that rising commodity prices, as world markets experience a commodity boom, are the main cause of the agricultural growth. Others point to improvements in the policy environment and increased investments in agriculture at a time when African governments and donors have been rallying to increase their support to agriculture. Is African agriculture undergoing a new and sustained recovery after many decades of stagnant and volatile growth rates—or is it simply riding the current global commodity boom? We attempt to answer this question by analyzing the structure of overall agricultural growth in the past 30 years using a growth decomposition approach. Results show both good and bad news for future prospects of African agricultural growth. The good news is that a changing policy environment and increased attention to agriculture has had a major effect on overall productivity growth based on technical efficiency gains. The bad news is that most of this productivity growth is the result of countries recovering from the poor performance of the 1980s and 1990s together with favorable domestic prices. A key challenge for African countries in the years to come is to transform the current windfall gains from favorable high commodity prices and the one-time effects of policy reforms into sustainable growth based on technical change.